FROM EARLY CHILDHOOD TO PRIMARY SCHOOLS: A REVIEW OF TRANSITION PRACTICES FOR CHILDREN WITH AUTISM SPECTRUM DISORDER - Zahri, Amira Farzana; Zainal, Mohd Syazwan (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
The transition from early childhood settings to primary school represents a pivotal stage for children with disabilities, often characterized by emotional, social, systemic, and educational challenges. This review synthesizes existing literature to outline a multilevel framework for supporting these transitions, with a particular emphasis on developmental disabilities such as Autism Spectrum Disorder (ASD). Common barriers include limited teacher preparedness, inadequate inter-agency coordination, rigid curricula, restricted access to early intervention, and persistent social stigma. For children with ASD, these difficulties are further magnified by social exclusion, bullying, and fragmented service continuity, leading to heightened anxiety and emotional dysregulation. Evidence highlights the role of early intervention centers in promoting school readiness through individualized plans, collaborative family-professional partnerships, and structured programs. Effective strategies include transition planning meetings, targeted teacher training, peer-mediated approaches, and parent empowerment initiatives that demonstrate the value of socially validated, classroom-embedded practices. Importantly, the success of such efforts depends on sustained collaboration among schools, families, service providers, and policymakers. This review emphasizes the need for inclusive, child-centered practices that are tailored to individual strengths and initiated well before school entry. Addressing systemic shortcomings, enhancing teacher capacity, and reducing stigma through coordinated policy reform are critical to ensuring continuity and equity in education. By conceptualizing an integrated framework, this article advocates for proactive, holistic approaches that safeguard positive transitions and support the long-term well-being of children with disabilities.